The Rise and Efficiency of Low Field Portable MRI Scanners - Pires, Tancia; M.M, Jaseemudheen (Journal of Health and Allied Sciences NU, 2023)
Since the discovery of magnetic resonance imaging (MRI) as an imaging modality, it has evolved immensely and is still doing so. Most imaging modalities have made bedside or emergency imaging possible due to their portability. This aspect is yet to be fully evaluated and established in the case of MRI as its high-field strength requires specialized infrastructure and its time-consuming nature makes its portability questionable. The goal of this review is to access the efficiency and feasibility of low-field portable MRI (pMRI) systems in a wide array of health care applications. Articles from indexed journals, on PubMed, Springer, Elsevier, etc. databases, relevant to this study were searched and reviewed. This review provides an atypical design that could be used in making a pMRI unit that could find its potential in diagnosing a wide variety of pathologies with an added advantage of imaging critical patients in the intensive care unit or patients in isolation due to its portability, imaging patients with implants or prosthesis effectively due to its low field, pediatric imaging due to its high speed, for guided interventions, imaging obese and claustrophobic patients due to its open nature, in dental imaging, extremity scanning, etc. With its vast spectrum of applications in the health care system, the future of low-field pMRI units seems to be bright.
Keywords: bedside imaging; extremity MR imaging; low-field MRI; magnetic resonance imaging; portable MRI